New Approaches for Solving Fokker Planck Equation on Cantor Sets within Local Fractional Operators - Hassan Kamil Jassim (Journal of Mathematics)
We discuss new approaches to handling Fokker Planck equation on Cantor sets within local fractional operators by using the local fractional Laplace decomposition and Laplace variational iteration methods based on the local fractional calculus. The new approaches maintain the efficiency and accuracy of the analytical methods for solving local fractional differential equations. Illustrative examples are given to show the accuracy and reliable results.